Carbon-14 in the marine environment of Ringhals nuclear power plant - Eriksson Stenström, Kristina; Mattsson, Sören; Pédehontaa-Hiaa, Guillaume ; 0000-0003-2317-2035; Käll, Filip (Strålsäkerhetsmyndigheten, 2025)
The C-14 results from the study demonstrate that, although the liquid discharges from the Ringhals Nuclear Power Plant (NPP) are assumed to be small compared to the total operational C-14 releases, the resulting C-14 levels in marine biota can be substantially higher than in terrestrial biota. The fndings indicate that the chemical speciation of discharged C-14 plays a critical role in its transfer and uptake by marine organisms. The highest concentrations of C-14 were observed near the cooling water outlet of the NPP. Organisms collected from a biofouling plate exhibited F14C1 values up to approximately 700% above the estimated marine background. Similarly, soft tissue from Symphodus melops (corkwing wrasse) showed up to ~400% excess, Mytilus edulis (blue mussel) up to ~170%, and Fucus vesiculosus (bladderwrack) up to ~100%.
Keywords: carbon-14; environmental monitoring; nuclear power plant